Pharmacokinetics, Safety and Tolerability of JNJ-56136379, a Novel Hepatitis B Virus Capsid Assembly Modulator, in Healthy Subjects - Vandenbossche, Joris; Jessner, Wolfgang; van den Boer, Maarten; Biewenga, Jeike; Berke, Jan Martin; Talloen, Willem; De Zwart, Loeckie; Snoeys, Jan; Yogaratnam, Jeysen (Advances in therapy, 2019)
Introduction Hepatitis B viral capsid assembly is an attractive target for new antiviral treatments. JNJ-56136379 (JNJ-6379) is a potent capsid assembly modulator in vitro with a dual mode of action. In Part 1 of this first-in-human study in healthy adults, the pharmacokinetics (PK), safety and tolerability of JNJ-6379 were evaluated following single ascending and multiple oral doses. Methods This was a double-blind, randomized, placebo-controlled study in 30 healthy adults. Eighteen subjects were randomized to receive single doses of JNJ-6379 (25 to 600 mg) or placebo. Twelve subjects were randomized to receive 150 mg JNJ-6379 or placebo twice daily for 2 days, followed by 100 mg JNJ-6379 or placebo daily for 10 days. Results The maximum observed plasma concentration and the area under the curve increased dose proportionally from 25 to 300 mg JNJ-6379. Following multiple dosing, steady-state conditions were achieved on day 8. Steady-state clearance was similar following single and multiple dosing, suggesting time-linear PK. All adverse events (AEs) reported were mild to moderate in severity. There were no serious AEs or dose-limiting toxicities and no apparent relationship to dose for any AE. Conclusion JNJ-6379 was well tolerated in this study. Based on the safety profile and plasma exposures of JNJ-6379 in healthy subjects, a dosing regimen was selected for Part 2 of this study in patients with chronic hepatitis B. This is anticipated to achieve trough plasma exposures of JNJ-6379 at steady state of more than three times the 90% effective concentration of viral replication determined in vitro. Trial registration Clinicaltrials.gov identifier, NCT02662712. Funding Janssen Pharmaceutica.